Rabiz: the unintended child of 1960s’ urban culture - H. Bayadyan (Ukrainian Cultural Studies, 2019)
The article discusses the ideological, social and cultural conditions that made possible the formation and development of "rabiz," a form of urban musical folklore, in the 1960s. Rabiz is described as an undesired result of the Socialist modernization process. It had received certain important aspects from the preserved forms of pre-Soviet urban culture but for some of its key features owes to the soviet cultural policy of the 1930s and the socio-cultural tendencies of the Soviet Armenia of the 1960s and 1970s. Rabiz was a side effect of the industrialization and urbanization of the 60s and was then radically transformed and degraded during the process of post-Soviet deindustrialization.